Analisis Potensi Ancaman Siber pada Bidang Ekonomi di Indonesia - Rahakbauw, Isro' Kurniawan (Jurnal Kajian Stratejik Ketahanan Nasional, 2024)
This article discusses the analysis of potential cyber warfare threats in the economic sector in Indonesia. The increasing dependence on information technology and widespread connectivity opens wide doors for potential cyber attacks on the country's economic sector. Through an analytical approach, this article explores various potential cyber threats that Indonesia may face, involving attacks on financial infrastructure, electronic commerce, as well as business data and information. In this context, the article also evaluates the readiness and effectiveness of cybersecurity measures implemented by the government and the private sector. Findings from this analysis provide valuable insights to identify and address potential cyber threats in Indonesia's economic sector, emphasizing the importance of improvements and strengthening in national cybersecurity policies.